Recovery of Microsclerotia of Verticilium dahliae from Soil as Subjected to Various Treatments - Loekas Soesanto; A. J. Thermorshuizen (Universitas Gadjah Mada, 2002)
The influence of various conditions on the survival of microsclerotia of Verticilium dahliae Kleb. was studied using three sources of field-collected potato stems densely covered with naturally-formed microsclerotia. Microsclerotia were found to survive for up 2 years in potato stems not incorporated in soil. The effects of temperature, pF, including weekly variations in temperature and or pF, and various modes of incorporating potato stem tissue on the survival of microsclerotia for up to 1 year in a sandy unsterilised soil was also studied for different microsclerotia sources. Inoculum source had no signicant effect. Remarkably few microslcerotia were recovered one day after the start of experiments varying between 5.5 and 31%. Recovery remained at this level or even decreased for another month and for several treatments, also after 3 and 6 months. Only after 3 to 12 months, recovery increased to values up to 5 times higher than that of one day after start of the experiment, but recoveries did not exceed the number of microsclerotia initially incorporated into the soil. Changes in recovery may be due to variation in the level of soil mycostasis which is affected by rate of nutrient exudation from microsclerotia.